Arctic influence on mid-latitude weather and climate: recent progress and future prospects - Semmler, Tido; Jung, Thomas (Zenodo, 2019)
Keynote presentation at the EMS General Assembly in Lyngby, Denmark, 9th to 13th of September, 2019.